Influence of Local Sources and Meteorological Parameters on the Spatial and Temporal Distribution of Ultrafine Particles in Augsburg, Germany - Giemsa, Esther; Soentgen, Jens; Kusch, Thomas; Beck, Christoph; Münkel, Christoph; Cyrys, Josef; Pitz, Mike (Frontiers in Environmental Science, 2021)
Ultrafine particles (UFP; diameter less than 100 nm) are ubiquitous in urban air, and an acknowledged risk to human health. At the same time, little is known about the immission situation at typical urban sites such as high-traffic roads, residential areas with a high amount of solid fuels for home heating or commercial and industrial areas due to missing legal requirements for measurements of UFP. Therefore, UFP were measured and evaluated in the (sub-)urban background as well as on spots influenced by these various anthropogenic local sources in the city of Augsburg, Germany, for the year 2017. In particular, the spatial and temporal correlations of the UFP concentrations between the seven measurement sites, the quantification and valuation of the contribution of local emitters with regard to their diurnal, weekly and seasonal variations and the influence of meteorological conditions on the formation and dispersion of UFP were investigated. Our analysis results demonstrate that urban UFP concentrations show a pronounced temporal and spatial variability. The mean concentration level of UFP varies between below 8,000 ultrafine particles/cm3 at the suburban background site and above 16,700 ultrafine particles/cm3 at the measurement station located next to a busy street canyon. At this particularly traffic-exposed measurement station, maximum concentrations of over 50,000 ultrafine particles/cm3 were measured. The additional UFP load caused by intensive traffic volume during evening rush hour in connection with the unfavourable exchange processes in the street canyon can be quantified to concentrations of 14,000 ultrafine particles/cm3 on average (compared to the immission situation of the urban background). An aggravating effect is brought about by inversion weather conditions in connection with air-polluted easterly winds, low wind speeds, lack of precipitation and very low mixing layer heights, such as over Augsburg at the end of January 2017, and cause peak concentrations of UFP.